Sikap Remaja Muslim terhadap Iklan dalam Drama Korea (Studi pada Siswa-Siswi SMA Muhammadiyah 1 dan Madrasah Aliyah Negeri Godean Yogyakarta terhadap Product Placement Aplikasi LINE dalam Drama Korea “Man From Another Star”) - Virga, Rika Lusri (Pascasarjana IAIN Lhokseumawe, 2019)
This research tend to describe the product placement as one of strategy from marketing either through soap operas or movies. Today, so many products of Korean culture come to Indonesia. Whether the fashion products, automotive, electronic, mobile phone until the Korean food. Through product placement, all of the product in Kdrama (Korea drama) or the soap operas from korea. In this research its Man From Another Star, released in 2014. It has so many brands from Korean products. One of them is social media applications called LINE. The brand shown in every scene of Kdrama. In Indonesia, the big audiens are young people (15- 20). From this fact, researcher has interest to know how the attitude of Moslem youth toward the product placement advertising of Line application in the drama. This research use Quantitative methods with descriptive survey. Sample from this research is sudents from senior high school Muhammadiyah 1 Yogyakarta and MAN Godean 1 Yogyakarta. The results from the research showed the attitude of the public in obtaining the cognitive component of attitude is positive results. While affective and conative components to obtain results quite negative attitude.